Advertising in the program “En Surco la basura sirve” and its socio-educational effect in solid residues recollection in Santiago de Surco District (2012-2013) - Carranza Salanitro, Lilian (2017)
People from Lima generate 8,000 tons of garbage a day; throwing solid, inorganic and non-biodegradable waste that pollute the environment, altering negatively their habitat conditions and generating serious problems in their health, life, economy and culture. In this context; the current investigation is carried out; considering the actual ecology and environment legal norm. The effect in reference has non-formal character; it is manifested in the memory and understanding of the advertisement; classification of the source of household solid waste; identification, degree of affinity, positioning, and evaluation of the program: “En Surco la basura sirve” and public management of The Empresa Municipal de Santiago de Surco (EMUSSA).